The Relationship between Grade-Level and Breakfast Skipping among Adolescents: The Mediating Effects of Dietary Autonomy - Jamil M. Lane; Silvia Sörensen (New Prairie Press, 2022)
Breakfast skipping among adolescents in the United States is a public health issue because it has adverse consequences on dietary intake and body mass index. The primary aim of this study is to examine the relationship between grade level and reported breakfast skipping among adolescents and whether it is mediated by dietary autonomy. Analyses were based on self-reported data from Wave I of the National Longitudinal Study of Adolescent Health, a nationally representative sample of adolescents in the United States surveyed in 1995. Logistic regression analysis was used to evaluate the effects of grade level and dietary autonomy on adolescents' reported breakfast skipping. Following MacKinnon and Dwyer, we tested whether the effect of grade level on breakfast skipping was mediated by adolescents' dietary autonomy. After controlling for sex, race, exercise, parental education, and household income, both grade level (OR = 2.005, 95% CI = 1.684-2.387) and dietary autonomy (OR = 1.435, 95% CI = 1.157-1.780) were each significant predictors of breakfast skipping when tested separately. Mediation analysis showed that dietary autonomy partially mediated the relationship between grade-level and breakfast skipping. Since adolescents in higher grades and those with more dietary autonomy are more likely to skip breakfast, nutritional messages may need to continue beyond the lower grades and emphasize that healthy eating habits can demonstrate autonomy.